Gene Expression Profiling of 1α, 25(OH)2D3 Treatment in 2D/3D Human Hepatocyte Models Reveals CYP3A4 Induction but Minor Changes in Other Xenobiotic‐Metabolizing Genes. Issue 9 (1st March 2022) - Pavek, Petr; Dusek, Jan; Smutny, Tomas; Lochman, Lukas; Kucera, Radim; Skoda, Josef; Smutna, Lucie; Kamaraj, Rajamanikkam; Soucek, Pavel; Vrzal, Radim; Dvorak, Zdenek
Abstract : Scope: CYP3A4 is the most important drug‐metabolizing enzyme regulated via the vitamin D receptor (VDR) in the intestine. However, less is known about VDR in the regulation of CYP3A4 and other drug‐metabolizing enzymes in the liver. Methods and Results: This study investigates whether 1α, 25‐dihydroxyvitamin D3 (1α, 25(OH)2 D3 ) regulates major cytochrome P450 enzymes, selected phase I and II enzymes, and transporters involved in xenobiotic and steroidal endobiotic metabolism in 2D and 3D cultures of human hepatocytes. The authors found that 1α, 25(OH)2 D3 increases hepatic CYP3A4 expression and midazolam 1′‐hydroxylation activity in 2D hepatocytes. The results are confirmed in 3D spheroids, where 1α, 25(OH)2 D3 has comparable effect on CYP3A4 mRNA expression as 1α‐hydroxyvitamin D3, an active vitamin D metabolite. Other regulated genes such as CYP1A2, AKR1C4, SLC10A1, and SLCO4A1 display only mild changes in mRNA levels after 1α, 25(OH)2 D3 treatment in 2D hepatocytes. Expression of other cytochrome P450, phase I and phase II enzyme, or transporter genes are not significantly influenced by 1α, 25(OH)2 D3 . Additionally, the effect of VDR activation on CYP3A4 mRNA expression is abolished by natural dietary compound sulforaphane, a common suppressor of pregnane X receptor (PXR) and constitutive androstane receptor (CAR). Conclusion: This study proposes that VDR or vitamin D supplementation is unlikely to significantly influence liver detoxification enzymes apart from CYP3A4. Abstract : Few enzymes providing drug clearance were found under the control of activated vitamin D receptor in the liver. We investigated whether active vitamin D3 regulates major detoxification enzymes and transporters in 2D and 3D cultures of human hepatocytes. We show that VDR or vitamin D supplementation is unlikely to significantly influence drug elimination apart from the regulation of CYP3A4 enzyme.